2017
DOI: 10.3389/fnhum.2017.00008
|View full text |Cite
|
Sign up to set email alerts
|

Human Brain Activity Related to the Tactile Perception of Stickiness

Abstract: While the perception of stickiness serves as one of the fundamental dimensions for tactile sensation, little has been elucidated about the stickiness sensation and its neural correlates. The present study investigated how the human brain responds to perceived tactile sticky stimuli using functional magnetic resonance imaging (fMRI). To evoke tactile perception of stickiness with multiple intensities, we generated silicone stimuli with varying catalyst ratios. Also, an acrylic sham stimulus was prepared to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…For seed-based FC analyses, a whole-brain approach was used to identify cortical areas that were differentially connected with bilateral SI and SII among four conditions (5, 25, 65 cm/s, and "All ON"). The four seeds (see Table 1) were chosen based on the literature (Lin and Kajola, 2003;Pastor et al, 2004;Reed et al, 2004;Dresel et al, 2008;Ackerley et al, 2012;Popescu et al, 2013;Custead et al, 2017;Oh et al, 2017;Yeon et al, 2017) because bilateral SI and SII were most consistently identified across imaging studies with different parameters. We chose to compute all possible cross-correlation coefficients between the time series of the seeds and all residual voxels in the brain, and 3 http://www.nitrc.org/projects/artifact_detect/ then convert them to Z-scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For seed-based FC analyses, a whole-brain approach was used to identify cortical areas that were differentially connected with bilateral SI and SII among four conditions (5, 25, 65 cm/s, and "All ON"). The four seeds (see Table 1) were chosen based on the literature (Lin and Kajola, 2003;Pastor et al, 2004;Reed et al, 2004;Dresel et al, 2008;Ackerley et al, 2012;Popescu et al, 2013;Custead et al, 2017;Oh et al, 2017;Yeon et al, 2017) because bilateral SI and SII were most consistently identified across imaging studies with different parameters. We chose to compute all possible cross-correlation coefficients between the time series of the seeds and all residual voxels in the brain, and 3 http://www.nitrc.org/projects/artifact_detect/ then convert them to Z-scores.…”
Section: Discussionmentioning
confidence: 99%
“…The human somatosensory system decodes tactile stimuli from peripheral sensory receptors through a complex process involving interactions between bottom-up thalamocortical and topdown corticocortical/cortico-thalamo-cortical pathways (Avivi-Arber et al, 2011;Lundblad et al, 2011;Zembrzycki et al, 2013;Hwang et al, 2017). Studies of cortical representations of tactile stimulation of different body parts have identified the primary (SI) and secondary (SII) somatosensory cortices, as well as the supplementary motor area responsible for sensory processing (Ibáñez et al, 1995;Backes et al, 2000;Grodd et al, 2001;Backlund et al, 2003;Paus et al, 2006;Backlund Wasling et al, 2008;Bjornsdotter et al, 2009;Ackerley et al, 2012;Zembrzycki et al, 2013;Akselrod et al, 2017;Custead et al, 2017;Oh et al, 2017;Yeon et al, 2017). SI, which is located in the postcentral gyrus, processes complex information about the location, velocity, and other characteristics of tactile stimulation from the thalamus through the thalamocortical axons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous fMRI study, we successfully found brain regions exhibiting correlations of blood oxygen level-dependent (BOLD) signals with perceived tactile stickiness using conventional uni-variate analyses and an in-house sticky stimulus set (Yeon et al, 2017 ). Based on the psychophysical experimental results on our stimulus set, the sticky stimuli were divided into three disjoint groups in terms of perceptual intensity: Supra-threshold (sticky stimuli that can consistently evoke sticky sensation), Infra-threshold (sticky stimuli that barely evoke sticky sensation), and Sham (tactile stimuli that contain no sticky property) groups.…”
Section: Introductionmentioning
confidence: 99%
“… Our previous human fMRI study found brain activations correlated with tactile stickiness perception using the uni-variate general linear model (GLM) (Yeon et al, 2017 ). Here, we conducted an in-depth investigation on neural correlates of sticky sensations by employing a multivoxel pattern analysis (MVPA) on the same dataset.…”
mentioning
confidence: 99%